2005
DOI: 10.1016/j.ejpb.2005.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Silk fibroin as a novel coating material for controlled release of theophylline

Abstract: The aim of this study was to explore potential use of the silk fibroin (SF) as an aqueous coating material for theophylline tablets. We have examined the film forming and coating properties of heat-treated fibroin, SF solution having different amounts of polyethylene glycol (PEG) and 1-ethyl-3-(3-dimethyl aminopropyl)carbodiimide (EDC) cross-linked SF. Heat-treated SF material possessed a brittle structure, which resulted in poor film forming and coating properties. The optimum PEG amount in SF solution was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(50 citation statements)
references
References 40 publications
1
48
0
1
Order By: Relevance
“…Silk fibroin is an edible protein polymer which has functional aminoacids in its structure, and it is preferred in many biotechnological applications such as drug delivery and tissue engineering [30][31][32]. Its hydrophobic character makes it favorable adsorbent used in adsorption studies [33].…”
Section: Introductionmentioning
confidence: 99%
“…Silk fibroin is an edible protein polymer which has functional aminoacids in its structure, and it is preferred in many biotechnological applications such as drug delivery and tissue engineering [30][31][32]. Its hydrophobic character makes it favorable adsorbent used in adsorption studies [33].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, HA is a natural anionic polysaccharide that has been used in the formation of PECs. It is thought as an attractive building block for the production of novel biomaterials with potential applications in drug delivery [19][20][21][22] and tissue engineering [23]. The specific objective of this work was to characterize the films produced by complex formation between SF and HA.…”
Section: Introductionmentioning
confidence: 99%
“…Methanol treatment is a widely used process to induce β-sheet formation although it does not transform all molecular regions. Ethanol, EDC, glutaraldehyde, and genipin cause the transition from random coils to β-sheet configurations of the scaffolds and is dependant on the length of time exposed to the solvent as well as the solvent concentration [112][113][114][115][116]. Studies have shown that regenerated silk fibers can hold their initial tensile integrity for 21 days under immune deficient in vitro culture conditions [117].…”
Section: Silk Fibroinmentioning
confidence: 99%